Common unresolved problem with the EMS and EMU. - SALVATORE, Dominic (1997)
Points out that although establishing the EMU will overcome some of the pitfalls of the EMS which delayed the cause of monetary union in Europe, it will face the same basic problem as the EMS. Specifically, the EMS crises reinforced the belief that a nation cannot simultaneously have fixed exchange rates, unrestricted international financial capital flows, and even a semi-autonomous monetary policy.